2019
DOI: 10.1080/14616734.2019.1680713
|View full text |Cite
|
Sign up to set email alerts
|

Predicting infant–father attachment: the role of pre- and postnatal triadic family alliance and paternal testosterone levels

Abstract: This longitudinal study examined whether prenatal family alliance and prenatal paternal testosterone levels predicted infant-mother and infant-father attachment security and whether this association was mediated by postnatal family alliance and postnatal paternal testosterone levels. In 105 couples expecting their first child, family alliance was assessed in the third trimester of pregnancy with the prenatal version of the Lausanne Trilogue Play (LTP). Family alliance was measured again 6 months postnatally, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…Fathers' perinatal behaviour and involvement during pregnancy is known to benefit maternal health behaviours and foetal outcomes (see Alio, Salihu, Kornosky, Richman and Marty, 2010;Lamb, 2010, for reviews) and the quality of later affective and behavioural involvement with his children (e.g. N. Cabrera et al, 2008;Cook et al, 2005;Fagan et al, 2007;Witte et al, 2019). Additionally, parenting sensitivity originates in the prenatal period (Leifer, 1977;Lucassen et al, 2015;Steele et al, 1996) and early postnatal parenting quality is likely founded on prenatal mental representations of the unborn child as well as the caregiver's imagined (future) relationship with the child (Siddiqui & Hägglöf, 2000;Vreeswijk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fathers' perinatal behaviour and involvement during pregnancy is known to benefit maternal health behaviours and foetal outcomes (see Alio, Salihu, Kornosky, Richman and Marty, 2010;Lamb, 2010, for reviews) and the quality of later affective and behavioural involvement with his children (e.g. N. Cabrera et al, 2008;Cook et al, 2005;Fagan et al, 2007;Witte et al, 2019). Additionally, parenting sensitivity originates in the prenatal period (Leifer, 1977;Lucassen et al, 2015;Steele et al, 1996) and early postnatal parenting quality is likely founded on prenatal mental representations of the unborn child as well as the caregiver's imagined (future) relationship with the child (Siddiqui & Hägglöf, 2000;Vreeswijk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This did not allow examination whether pre-natal triadic family relations might predict mother-and father-child attachment relationship. As regard this issue, a recent investigation has shown that children's attachment toward fathers (but not toward mothers) is predicted by pre-natal triadic family alliance, that is by the ability of the mother and father to cooperate and support each other in their parental roles (79).…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…Moreover, studies on parents-to-be are still lacking. Experimental designs using a life-like doll have been proposed to examine the responsiveness of both childless participants and parents [ 4 , 5 ]. Hence, the presented research project focuses on expectant vs. non-expectant couples reacting to a life-like doll and, as a continuation, on the sensitive responsiveness of these new parents towards their children.…”
Section: Introductionmentioning
confidence: 99%